Fate of antibiotics and the related antibiotic resistance genes during sludge stabilization in sludge treatment wetlands. (June 2019) - Ma, Junwen; Cui, Yubo; Zhang, Wanjun; Wang, Chao; Li, Aimin
Abstract: Antibiotics contamination and related antibiotics resistance genes (ARGs) in wastewater sludge have been a concern for environmental pollution and human health risk for years. This study investigated the fate of antibiotics and related ARGs in sludge from sludge treatment wetlands (STWs). We examined three sludge treatment beds i.e. unit No.1 was sludge drying bed with aeration tubes; unit No.2 was a ventilated sludge drying reed bed; and the unit No.3 was a sludge drying reed bed without aeration tubes. The targeted antibiotics included oxytetracycline, roxithromycin and azithromycin. The targeted ARGs included tetA, tetC, msrSA and ermB. The results indicated that in all three units antibiotics were removed significantly and related ARGs declined over one year period. The antibiotics concentrations in the surface layer were lower than those in the bottom layer. The highest removal efficiency of the targeted antibiotics was observed in the unit No.2. The removal efficiency of the targeted ARGs influenced by different parameters, especially reeds, aeration tubes and temperature. Correlation analysis between the concentrations of antibiotics and corresponding ARGs showed that in both the bottom and surface layer of all three units, a significant correlation (p < 0.05) was found between the concentrations of roxithromycin and azithromycin and the absolute abundances of msrSA. A significant correlation (p < 0.05) was also observed between the concentrations of oxytetracycline and the absolute abundances of tetA and tetC. The results demonstrated that STWs can effectively reduce the target antibiotics contents and related ARGs; and the STW with reed and aeration tubes performed better. Highlights: Three STWs were different due to the presence of reeds and aeration tubes. All three STWs could remove antibiotics and related ARGs effectively. Planted unit with aeration tubes showed higher removal rate in pollutants. The content of antibiotics was correlated with the abundances of related ARGs.